RNA polymerase pausing and nascent RNA structure formation are linked through clamp domain movement - Hein, Pyae P. (2014)
The rates of RNA synthesis and nascent RNA folding into biologically active structures are linked via pausing by RNA polymerase (RNAP). Structures that form within the RNA exit channel can increase pausing by interacting with bacterial RNAP or decrease pausing by preventing backtracking. Conversely, pausing is required for proper folding of some RNAs. Opening of the RNAP clamp domain is proposed to mediate some effects of nascent RNA structures. However, the connections among RNA structure formation, clamp movement, and catalytic activity remain uncertain. We assayed exit-channel structure formation in Escherichia coli RNAP together with disulfide crosslinks that favor closed or open clamp conformations and found that clamp position directly influences RNA structure formation and catalytic activity. We report that exit-channel RNA structures slow pause escape by favoring clamp opening and through interactions with the flap that slow translocation.